EDUCATING CHILDREN BY UNDERSTANDING THEIR DEVELOPMENTAL PSYCHOLOGY - Suciati Suciati (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2016)
Children are figures that parents do the best for them. The most valuable thing given by parents to children is education. In educating and teaching children, especially elementary students, parents and teachers often find it difficult. Lack of motivation is the reason children are always first and foremost. To increase their motivation, parents and teachers need to understand the psychology of child development. Elementary school age children have different developmental psychology characteristics. These characteristics are classified into four points: physical, social, language, and cognitive. By understanding the characteristics of psychological development of children, parents and teachers must teach and educate children in accordance with their development and not do things that are unwanted by children. It was proved that any children of different ages have different developmental psychology. By understanding the psychology of their development, parents and teachers can teach and educate them easily knowing what can make children motivated and to obtain the best results in education, parents and teachers or schools to work together.